Greater discomfort with blood flow restriction training compared to standard low-load resistance exercise when both are performed to task failure - Pignanelli, C.; Burr, J. F. (Translational Sports Medicine, 2020)
Low-load blood flow restriction (LL-BFR) training improves muscular adaptation compared to traditional low-load resistance exercise (LL-RE), when matched for work. However, when both are performed to task failure, similar improvements in muscular strength and hypertrophy occur. At task failure, the perceived discomfort after a single bout of LL-BFR or LL-RE is equivocal and it remains unclear how this might change over time with training. Therefore, we examined alterations in the perception of discomfort during LL-RE and LL-BFR training. Ten resistance-trained males performed both LL-RE and LL-BFR to failure, with each leg assigned to a different condition for 6 weeks. Perceived discomfort was obtained after each set and rest period during the 1st, 4th, 8th, 11th, and 15th training sessions using a 1000-pixel visual analog scale. Perceived discomfort was similar following each set for LL-RE and LL-BFR within each training session and did not change with training. At the end of rest periods, with the tourniquet still applied, a consistently greater discomfort was reported with LL-BFR (all P < .02), with no evidence for desensitization over time. Overall, participants reported similar discomfort following LL-RE and LL-BFR sets to failure; however, the application of BFR throughout rest periods increased discomfort, with no clear habituation with regular training.